Male Teachers’ Narratives: Experiences of Teaching in Early Childhood Education - Mahudi Mofokeng; B. N. Ndlovu (Studies in Social Science & Humanities, 2024)
Globally, women are over-represented in teaching in the early years of primary school, or the Foundation Phase, as it is known in South Africa (SA). We explore how male teachers in SA may experience challenges in teaching in primary schools that are complicit in reproducing men as managers. Men tend to be positioned within dominant notions of masculinity, which produce masculine power in school management, while primary teaching is characterised as ‘women’s work’. Teachers of both genders are complicit in safeguarding the primary school as a nurturing, female domain while reproducing gendered binaries and unequal power relations. Through semi-structured interviews and a focus group discussion, we explore the experiences of five male early childhood development (ECD) teachers from five rural primary schools in diverse settings in Free State, SA. Males have challenges in ECD as they are not allowed to teach but are encouraged to be involved in management, where they may sit on different school committees such as those related to sport and discipline, and also take care of the school premises. There is a need to create alternate masculinities beyond rigid notions of appropriate gender performances and address social challenges such as the paucity of male teachers, children being exposed to only one gender, and gender transformation in SA. In this way, the challenges facing male ECD teachers, who are not being entirely accepted in this field, will be eliminated.